An experimental work on the impact of new combinations of solar chimney, photovoltaic and geothermal air tube on building cooling and ventilation. (15th July 2020) - Elghamry, Rania; Hassan, Hamdy
Highlights: Maximum total daily ventilated air is achieved in case of the forced geothermal air tube. Minimum daily ventilated air occurs in case of natural geothermal air tube with chimney inclination angle 30°. Maximum ventilated air and heat released from the room is achieved at chimney inclination angle 45°. Maximum PV output power for the PV inside the chimney is obtained at chimney inclination angle 30°. PV output power inside the chimney represents around 70% of the PV output power outside the chimney. Abstract: Renewable energy applications play a major role in covering the energy demand for building cooling and ventilation. In this paper, an experimental investigation is performed on cooling and ventilation of a building room locating in New Borge Alarb city, Alexandria, Egypt by new combination of solar chimney and geothermal air tube heat exchanger system. PV panel is installed by new technique at the chimney back to produce power and its performance is compared to an identical PV outside the room. The study is performed for the chimney and PVs facing south of an angle with the horizontal 30° and 45° and for natural and forced airflow inside the geothermal tube. The geothermal tube and chimney ventilation systems are compared with the natural ventilation system of the solar chimney and window. The results indicate that the proposed systems prove their ability to cool the room temperature up to 3.5 °C and change daily its air 42 times. Minimum ventilated air occurs at natural geothermal tube-chimney system of angle 30°. The ratio of the total daily ventilated air by natural geothermal tube-chimney to that by chimney-window is about 56.3% and 65% at 30° and 45°, respectively and for heat released is 55.6% and 64%, respectively. Maximum daily heat released from the room is achieved at chimney inclination angle 45° for natural geothermal tube-chimney-PV system. Maximum PV output power inside the chimney represents 70% of the maximum PV output power outside the chimney which is 120 W/m 2 at chimney inclination angle 30°.